2004
DOI: 10.1103/physrevd.70.043510
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological model with macroscopic spin fluid

Abstract: We consider a Friedmann-Robertson-Walker cosmological model with some exotic perfect fluid with spin known as the Weyssenhoff fluid. The possibility that the dark energy may be described in part by the Weyssenhoff fluid is discussed. The observational constraint coming from supernovae type Ia observations is established. This result indicates that, whereas the cosmological constant is still needed to explain current observations, the model with spin fluid is admissible. For high redshifts z > 1 the differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…Then, unlike in [156], although the spin sector in EC framework plays an important role in the early stages of the universe with a repulsive gravitational effect, at late times the cosmological constant or dark energy term proposed by Padmanabhan is required again to achieve the holographic equipartition in this model. This fact is in agreement with the result obtained in [131] where the luminosity distance is implemented to test the models using the supernovae type Ia observations. There, the authors showed that although a cosmological model with a spin fluid is admissible, the cosmological constant is still required to explain the accelerating expansion of the universe.…”
Section: Emergence Of Spacetime In Einstein-cartan Theorysupporting
confidence: 80%
See 1 more Smart Citation
“…Then, unlike in [156], although the spin sector in EC framework plays an important role in the early stages of the universe with a repulsive gravitational effect, at late times the cosmological constant or dark energy term proposed by Padmanabhan is required again to achieve the holographic equipartition in this model. This fact is in agreement with the result obtained in [131] where the luminosity distance is implemented to test the models using the supernovae type Ia observations. There, the authors showed that although a cosmological model with a spin fluid is admissible, the cosmological constant is still required to explain the accelerating expansion of the universe.…”
Section: Emergence Of Spacetime In Einstein-cartan Theorysupporting
confidence: 80%
“…Similar to the other alternative theories of gravity, the cosmological solutions of the EC theory possessing the spin matter source and their influence on the structure and dynamics of the universe are extensively investigated. These studies include the effects of torsion and spinning matter in a cosmological setup and its possible role to solve the singularity problems, pre-Friedmann stages of evolution, inflationary expansion, the late time accelerated expansion of the universe, rotation of the universe, gravitational collapse, and so on [128][129][130][131][132][133][134][135][136][137][138][139][140].…”
Section: Introductionmentioning
confidence: 99%
“…In order to have better understanding of the new terms with θJ 2 in (3.26), we can consider the simplified cosmological model with vanishing ρ 0 and p 0 . It is easy to solve the Friedmann equation, H 2 = (8πG/3) ρ and obtain the corresponding rule for the expansion of the universe, 27) which, again, is different from the laws of expansion for free radiation (with a ∼ t 1/2 ) and dust (with a ∼ t 2/3 ). The results (3.23) and (3.27) do not depend on the value of BI parameter.…”
Section: Massless Casementioning
confidence: 99%
“…Following the Lagrangian formalism for this exotic spin fluid [22][23][24], one can see that the contribution from such fluid always produces a traceless torsion [25] (for the extensive discussion of the theories with spin fluid in cosmology, see also Refs. [26][27][28][29][30][31][32]). In this case the trace of the torsion tensor T µ = T α µα has smaller physical meaning and its presence is completely due to the nonminimal procedure [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Because this model unifies both the RSB model with vanishing dark radiation and the model with spinning fluid [39] we include this model to the class of models which are based on the modified FRW equation. Because the RSB and MAG models without the cosmological constant do not fit well the SNIa data [10,38,40] we also analyze the MAG and RSB models with the non-vanishing Λ term.…”
Section: Introductionmentioning
confidence: 99%